2019
DOI: 10.1007/s41207-019-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Can duckweed be used for the biomonitoring of textile effluents?

Abstract: 1In certain countries, poorly managed freshwaters need to be seriously controlled to not lead to ecosystems 2 degradation. This control can be achieved by a biomonitoring using living organisms as ecological alert 3 indicators. In this context, biotests were undertaken on Lemna gibba (L. gibba) to assess the toxic effect of 4 textile pollutants reaching a natural ecosystem. L. gibba were exposed to different concentrations (5-100 mg/L) 5 of two dyes, namely Direct Red 89 (DR-89) and Vat Blue 20 (VB-20), under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the presence of two textile dyes, Lemna giba, an aquatic macrophyte, had its growth rate and photosynthetic pigment content decreased. The authors of the study concluded that this species can be used as a bioindicator of polluting dyes [12]. High concentrations of dyes are reported to decrease vital elements, such as P, Mg, Ca, S, and Ca in plants of Eichhornia crassipes and Salvinia natans, which also presented damaged roots, chlorosis, and necrosis in leaves [13].…”
Section: Negative Impacts Of Textile Dyes On Human and Animal Healthmentioning
confidence: 99%
“…In the presence of two textile dyes, Lemna giba, an aquatic macrophyte, had its growth rate and photosynthetic pigment content decreased. The authors of the study concluded that this species can be used as a bioindicator of polluting dyes [12]. High concentrations of dyes are reported to decrease vital elements, such as P, Mg, Ca, S, and Ca in plants of Eichhornia crassipes and Salvinia natans, which also presented damaged roots, chlorosis, and necrosis in leaves [13].…”
Section: Negative Impacts Of Textile Dyes On Human and Animal Healthmentioning
confidence: 99%
“…The activated sludge (AS) used in the biodegradation tests were taken from the aeration tank of the municipal WWTP located in the city of Annaba (East Algeria). This sludge in the form of a suspension was transported in closed plastic containers to the laboratory and was suspended in a modi ed culture medium, necessary for the development of the microorganisms; it was then aerated under a moderate stirring, at ambient temperature T = 21 ± 1 °C at pH = 6.1 ± 0.1 (Hocini et al 2019). The suspension of the activated sludge was placed in a 1 L graduated cylinder (test tube) to allow it to settle.…”
Section: Activated Sludge Preparationmentioning
confidence: 99%
“…Furthermore, a slight reduction in the MDP was observed for the control as well as for the treatment solutions, compared with MDP of the activated sludge found in Table 1. This is probably due to the competition of the aquatic plants in the nutrient components and on the organic carbon obtained after the biodegradation of the target molecules, given that the growth of plants require different components, namely macro and micro elements that are indispensable for plant metabolism and for the complete development of their vegetative cycle (Hocini et al 2019;Kumar et al 2021).…”
Section: In Uence Of Aquatic Plants On the Development Of Activated Sludgementioning
confidence: 99%